Periodic solutions of second-order non-autonomous dynamical systems with vanishing Green's functions - Yongxin Jiang (Electronic Journal of Differential Equations, 2019)
In this article, we study the existence and multiplicity of positive periodic solutions for second-order non-autonomous dynamical systems when Green's functions are non-negative. The proofs are based on a nonlinear alternative principle of Leray-Schauder and the fixed point theorem in cones. Some recent results in the literature are generalized and improved.